IEMVT at the service of veterinary medicine and stock-keeping - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
L'Institut d'Elevage et de Medecine Veterinaire des pays Tropicaux (the Institute of Tropical Veterinary Medicine and Stock-keeping) IEMVT, France has an information department to collect and disseminate scientific and technical documentation on the...